Dimensionamiento de cubiertas industriales - Ballesteros Barocio, Porfirio; Rodríguez Cuevas, Neftalí; Sánchez, José Luis (My University, 1976)
The following discussion is a briof resume of a talk given at the Thin Shell Seminar in Chicago in March 1959. this is not intended to be a complete treatise on the analysis of hyperbolic paraboloid shells but has been prepared to give a physical picture of the structual action involved. Results obtained agree with the exact solution presented by F. Candela in the january 1955 issue of the ACI Journal as far as uniform loads are concerned.
Keywords: paraboloide hiperbólico; conoides; cilíndricas; arcos en celosía; marcos múltiples